Decision Support System to Help in Determining the Study Program Concentration for Higher Education Institution - Oktavia, Tanty; Madyatmadja, Evaristus Didik (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
The process of decision support for higher education institution to determine the concentration of study program becomes a significant problem because the student needs to analyse their interest, ability, and other factors as the qualification. A mistake in decision-making will be detrimental to the students’ education level, and it can even affect their future. This is a problem that occurs every semester, not only within the scope of the faculty but also in the university. Therefore, this research proposes a model to ease the higher education institution in determining a concentration of student using AHP and TOPSIS method. AHP method is a decision support system that can give weight on criteria of concentration and test its consistency. This method is to give weight for each criterion of student concentration majoring in Information System. TOPSIS method has a concept that the appropriate alternative has the shortest distance with a positive ideal solution and has the farthest distance with a negative ideal solution. Moreover, the criteria for choosing the concentration are multiple intelligences, GPA, course score, and TOEFL score. Weights obtained from AHP become the input value in the TOPSIS method in sorting the alternatives to be selected. Then, the result of the sorting is being calculated for its accuracy level. Based on the calculation of 93 sample of student’s concentration with AHP-TOPSIS method, 62 data are the same, so it results in the accuracy of 67%. An application with AHP-TOPSIS method can be used to help the university management in determining the concentration at Information System major for XYZ University.